2015
DOI: 10.1016/j.bbamcr.2014.12.017
|View full text |Cite
|
Sign up to set email alerts
|

Nanoclusters of the resting T cell antigen receptor (TCR) localize to non-raft domains

Abstract: In the last decade an increasing number of plasma membrane (PM) proteins have been shown to be non-randomly distributed but instead forming submicron-sized oligomers called nanoclusters. Nanoclusters exist independently of the ligand-bound state of the receptors and their existence implies a high degree of lateral organisation of the PM and its proteins. The mechanisms that drive receptor nanoclustering are largely unknown. One well-defined example of a transmembrane receptor that forms nanoclusters is the T c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 38 publications
(38 citation statements)
references
References 73 publications
2
36
0
Order By: Relevance
“…70 Biochemical and microscopy studies have revealed the localization of the T-cell receptor (TCR) outside the raft domain in a resting state and its translocation in the detergent-resistant membrane fraction during T-cell activation. 71 In contrast, Dinic et al 72 found TCR in the raft domains of resting T cells and the aggregation of these domains upon TCR engagement. The disparate results concerning the association of TCR with lipid rafts is probably due to the differing methodologies used for the study.…”
Section: Role Of Lipid Rafts In Lymphocyte Activationmentioning
confidence: 97%
See 1 more Smart Citation
“…70 Biochemical and microscopy studies have revealed the localization of the T-cell receptor (TCR) outside the raft domain in a resting state and its translocation in the detergent-resistant membrane fraction during T-cell activation. 71 In contrast, Dinic et al 72 found TCR in the raft domains of resting T cells and the aggregation of these domains upon TCR engagement. The disparate results concerning the association of TCR with lipid rafts is probably due to the differing methodologies used for the study.…”
Section: Role Of Lipid Rafts In Lymphocyte Activationmentioning
confidence: 97%
“…Biochemical and microscopy studies have revealed the localization of the T‐cell receptor (TCR) outside the raft domain in a resting state and its translocation in the detergent‐resistant membrane fraction during T‐cell activation . In contrast, Dinic et al .…”
Section: Role Of Lipid Rafts In Lymphocyte Activationmentioning
confidence: 99%
“…Since then, several studies have implicated these domains in a variety of innate and adaptive immune responses 166 . In these contexts, the key immune receptors, including the IgE receptor (FceRI), T-cell receptor 167 , and B-cell receptor 44 , were found in detergent soluble membrane fractions in resting or immature cells, but acquired detergent resistance following receptor activation, suggesting that translocation to membrane rafts is associated with active signalling through these receptors 168,169 . This notion is supported by co-enrichment in DRMs of the proximal signal transduction machinery downstream of the immune receptors, including lymphocyte-specific protein tyrosine kinase Lck or proto-oncogene tyrosine-protein kinase Fyn 163 , as well as a signalling adaptor protein LAT 43 .…”
Section: Physiological Functions Of Raftsmentioning
confidence: 99%
“…Cholesterol and SM are two lipids essential for CCR5 signaling and TCR nanoclustering (Mañes et al, 2001, Molnar et al, 2012. In resting T cells, these receptors nonetheless partition in different membrane phases, liquid-ordered (lo) for CCR5 (Molon et al, 2005) and liquiddisordered (ld) for TCR (Beck-Garcia et al, 2015). This differential phase segregation argues against direct CCR5/TCR interaction as a mechanism that influences TCR nanoclustering.…”
Section: Discussionmentioning
confidence: 99%
“…This antigenindependent TCR nanoclustering (Lillemeier et al, 2010, Schamel & Alarcon, 2013, Schamel et al, 2005, Schamel et al, 2006, Sherman et al, 2011 enhances antigenic sensitivity by increasing avidity to multimeric peptide-major histocompatibility complexes (Kumar et al, 2011, Molnar et al, 2012 and by allowing cooperativity between TCR molecules (Martín-Blanco et al, 2018, Martínez-Martín et al, 2009. TCRβ subunit interaction with cholesterol (Chol) and the presence of sphingomyelins (SM) are both essential for TCR nanoclustering (Beck-Garcia et al, 2015, Molnar et al, 2012. Replacement of Chol by Chol sulfate impedes TCR nanocluster formation and reduces CD4 + CD8 + thymocyte sensitivity to weak antigenic peptides (Wang et al, 2016).…”
Section: Introductionmentioning
confidence: 99%